Beliefs about Jinn, black magic and evil eye in Bangladesh: the effects of gender and level of education - Mullick, Mohammad S.I. (Mental health, religion & culture, 2013)
The study was aimed to examine beliefs among 320 attendees of a large University Hospital in Dhaka about Jinn, black magic and evil eye among Muslims in Bangladesh, using a self-completed questionnaire. The majority believed in the existence of Jinn (72%) and in Jinn possession (61%). In contrast, a relatively smaller proportion believed in the existence of black magic and evil eye (50% and 44%, respectively). Women were more likely than men to believe in the existence of Jinn and to cite religious figures as the treating authority for diseases attributed to affliction by black magic. Participants with a higher educational attainment were less likely than those with lower attainment to believe in jinn possession; or to believe that Jinn, black magic, or evil eye could cause mental health problems. Mental health care practitioners need to be mindful of these beliefs to achieve the best outcome for their patients.